Thermally developing flow of Al2O3-water nanofluid through regular N-sided polygonal ducts: A semi-analytic weighted residuals approach. (June 2017) - Arefmanesh, A.; Abbasian Arani, A.A.; Niroumand, A.
Highlights: A semi-analytical method is developed for developing flow in polygonal ducts. Closed-form solutions for the flow and temperature fields are obtained. Both constant wall temperature and uniform heat flux boundary conditions are used. Nusselt numbers along the axial direction for various duct geometries are presented. Heat transfer enhancement with increasing nanoparticles volume fraction is observed. Graphical Abstract: Abstract: A semi-analytical approach is proposed to solve the hydrodynamically fully developed and thermally developing flow and heat transfer of Al2 O3 -water nanofluid through N-sided polygonal ducts. Using the Galerkin weighted residuals method, closed-form solutions for the flow and temperature fields in various polygonal ducts for the constant wall temperature and uniform wall heat flux boundary conditions are obtained. Variations of the Nusselt number along the axial direction for different duct geometries and different volume fraction of the nanoparticles are presented. Comparisons of the results for special cases with the existing results from the literature indicate that the employed method is quite accurate. The results show that the heat transfer enhances with increasing the nanoparticles volume fraction.